0363 Efficacy of Cognitive Behavioral Therapy Delivered via Telemedicine vs. Face-to-Face: Preliminary Results from a Randomized Controlled Non-Inferiority Trial. (12th April 2019) - Arnedt, J Todd; Conroy, Deirdre A; Mooney, Ann J; Dubuc, Kelley; Yang, Alexander; Balstad, Sydney; Pace, Dari; Sen, Ananda; Eisenberg, Daniel
Abstract: Introduction: CBT for insomnia is highly effective, but few evidence-based modalities exist beyond face-to-face to facilitate dissemination. Telemedicine is increasingly an option, but its efficacy and acceptability for delivering CBT for insomnia is unknown. In an ongoing randomized controlled non-inferiority trial, we are comparing face-to-face with telemedicine (via the AASM SleepTM platform) delivery of CBT for insomnia for improving sleep and daytime functioning. In this study, we compared these modalities on sleep diary and select daytime outcomes for the initial 30 participants. Methods: Adults with chronic insomnia (22 women, mean age 51.6 ± 15.4 years) were recruited through advertisement and insomnia clinics and screened for disqualifying sleep, medical, and mental health disorders. Eligible participants were randomized to 6 sessions of CBT for insomnia delivered face-to-face (n=13) or via AASM SleepTM (n=17). Participants maintained the consensus sleep diary throughout treatment and completed pre- and post-treatment measures of daytime functioning (fatigue, depression, anxiety, and overall functioning). Results: Mixed ANOVAs showed no significant Group by Time interactions for any of the sleep diary or daytime functioning variables. However, main effects of Time were evident for all sleep diary measures: sleep latency (F=25.1, df=1, 28, p<.001); wake after sleep onset (F=37.0, df=1, 28, p<.001); total sleep time (F=7.9, df=1, 28, p<.009); and sleep efficiency (F=62.7, df=1, 28, p<.001). Similarly, significant pre-to post-treatment improvements were seen in fatigue (MFI-20 General Fatigue: 13.7 ± 4.2 to 10.3 ± 3.5, p<.001), depression symptoms (PHQ-9: 9.2 ± 4.8 to 4.1 ± 3.6, p<001), anxiety symptoms (GAD-7: 4.6 ± 4.0 to 2.3 ± 2.2, p<.001), and overall functioning (WSAS: 11.9 ± 10.8 to 7.1 ± 7.8, p<.001). Conclusion: Preliminary findings suggest that CBT for insomnia is equally efficacious when delivered via the AASM SleepTM platform vs. face-to-face. Recruitment is continuing to ensure adequate power for the non-inferiority analyses and to evaluate sustainability of gains over 12 weeks. Support (If Any): American Sleep Medicine Foundation Grant # 168-SR-17 (JT Arnedt)